Significant Factors of Construction Delays Among Contractors in Klang Valley and its Mitigation - Hasmori, Muhammad Fikri; Said, Ilias; Deraman, Rafikullah; Abas, Nor Haslina; Nagapan, Sasitharan; Ismail, Mohd Hanif; Khalid, Faisal Sheikh; Roslan, Ahmad Farhan (International Journal of Integrated Engineering, 2018)
Construction industry has become one of the greatest income provider as it has contributed to the Gross Domestic Product (GDP) for Malaysia. However, construction sector has been much affected by unexpected situation such as construction delays. Delays in construction industry is one of the common problems that happened to most construction projects. By considering all viewpoint from various parties that involves in construction process such as contractors, client, consultant and others, this research identified the major factor that contributes to delays in Klang Valley, Malaysia. Questionnaires were distributed among respondents that involved in construction project in Klang Valley. The process of data analysis was conducted by using descriptive statistic that ranked the mean value of factors that contributes to delays. By using the ranking method, financial difficulties were recognized as the most significant factor that caused delays. Thus, by using the same method, some mitigation action has been proposed in order to avoid time overrun in construction